The reality of the partnership between the school and family from the point of view of teachers and administrators in schools of outstanding students (A field study in Lattakia) - سلمان دعاء; ريما سعدي (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The current study aims to identify the reality of the partnership between the school and the family in the schools of the outstanding, and the most effective aspects of the partnership, in addition to identifying the difference between teachers and administrators in activating this partnership. The researcher followed the descriptive approach to achieve the objectives of the study, and the sample consisted of 74 teachers and administrators. The researcher used a questionnaire to measure the reality of the partnership between the school and family it including the following dimenions: parenting, communication, volunteering, decision-making, learning at home, cooperation, based on the Joyce Epstine model. the results showed that the reality of the partnership between the school and the family came at average level. There is differences in the answers of teachers and administrators to the study questionnaire in favor of the administrators.